2020
DOI: 10.1007/s11051-020-05032-0
|View full text |Cite
|
Sign up to set email alerts
|

Principles of convergence in nature and society and their application: from nanoscale, digits, and logic steps to global progress

Abstract: Knowledge, technology, and society as well as natural systems are increasingly coherent and complex, and new systems are continuously formed at their interfaces. Convergence is a problem-solving strategy to holistically understand, create, and transform a system for reaching a common goal, such as advancing an emerging technology in society. The systems may be either in natural, scientific, technological, economic, or societal settings. Convergence offers a unifying strategy applicable to all systems that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…The emergence of computer science as one of the top 20 subjects publishing in nanotechnology suggests a convergence of nanotechnology and computing science, for example, in areas such as artificial intelligence (AI) system design and the drive towards the 4th Industrial Revolution (4IR). Nanotechnology publications from computer science can also be a sign of nanotechnology convergence (Roco 2020 ). However, additional investigations need to be done to ascertain the existence and extent of the fusion of nanotechnology, biotechnology, information technology, and cognitive sciences (NBIC) in South Africa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of computer science as one of the top 20 subjects publishing in nanotechnology suggests a convergence of nanotechnology and computing science, for example, in areas such as artificial intelligence (AI) system design and the drive towards the 4th Industrial Revolution (4IR). Nanotechnology publications from computer science can also be a sign of nanotechnology convergence (Roco 2020 ). However, additional investigations need to be done to ascertain the existence and extent of the fusion of nanotechnology, biotechnology, information technology, and cognitive sciences (NBIC) in South Africa.…”
Section: Resultsmentioning
confidence: 99%
“…When the year 2019 is considered, the emergence of computer science as one of the top 20 subjects publishing in nanotechnology suggests that nanotechnology convergence (Roco 2020 ) is happening the country. In addition, it was observed that there is a high degree of author/researcher collaboration within nanoscience in South Africa; this may also suggest convergence of disciplines with nanoscience research, but we are not sure at this stage, one needs to investigate if these authors are collaborating across disciplines or within disciplines.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One characteristic of AI is that it is directly intervening in different organizational spheres with applications in a growing number of activities (Panch et al 2019 ; Cox 2021 ). Another particularity that highlights the value of this field of knowledge is that it is part of disruptive projects with high investments in research and development (R&D), such as the technological convergence project (NBICA) of the National Science Foundation (NSF), which also includes other fields of knowledge such as nanotechnology, biotechnology, information and communication technologies, cognitive sciences and, as already mentioned, AI (Roco 2020 ; Lee and Lim 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are already bibliometric mappings referring to this subject but these are of a specific nature and do not include the family of indicators used in this work (Munim et al 2020 ; Dhamija and Bag 2020 ; Guo et al 2020 ; Fosso Wamba et al 2021 ; Goodell et al 2021 ). In recent years, AI has steadily increased the production of scientific articles and is playing a central role in the changing global technological pattern that is affecting multiple spheres (Bainbridge and Roco 2016 ; Roco 2020 ). The AI space is so dynamically and disruptively evolving from both a technology, society and a business perspective that related analyses and meta-analyses (including bibliometric methodologies) need to also be periodically repeated, conducting multi-modal, multi-nodal, multi-lateral and multi-layer studies including bibliometrics, surveys, semi-structured interviews and case studies as well as Knowledge, Information and Data Analytics (KID ANALYTICS) with a prospective retrospective orientation (Industry 4.0, Industry 5.0 and Society 5.0, Quadruple and Quintuple Innovation Helix-centered (Carayannis et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%